Papillary Lesions in Breast Pathology Practice: Diagnostic Challenges and Practical Approach. A Six-Year Experience from a Tertiary Care Hospital - Jassar, Dr. Aneeta (International Journal of Innovative Research in Medical Science, 2017)
Aims and Objectives: 1. Retrospective study of papillary lesions of the breast diagnosed on core needle biopsies (CNB); 2. Correlation of CNB diagnosis with diagnosis on excision biopsy, using immunohistochemistry (IHC) for myoepithelial markers where appropriate. Methods: One hundred six cases of papillary lesions of the breast diagnosed on CNB over a six year period (from Jan 2010 to Dec 2016) were studied and correlated with their diagnosis on excision biopsy. Results: The pathologic diagnosis for the 106 papillary lesions obtained at core biopsy was benign in 89 cases, atypical in 11, and malignant in 6. Four of the 89 benign lesions were ‘upgraded’. The total upgrade rate for papillary lesions without atypia and with atypia was 4.49% (4/89 cases) and 45.4% (5/11 cases) respectively. The overall positive predictive value for malignancy (including DCIS) with core needle biopsy was 85.7% while the negative predictive value was 94.9%. All cases classified as malignant on CNB turned out to be malignant on excision biopsy. Conclusion: Papillary lesions of the breast are heterogeneous and CNB diagnosis can be diagnostically challenging due to limited sampling, difficulty in accurately characterizing atypia and conclusively ruling out in-situ or invasive components; potentially leading to an erroneous diagnosis. Therefore all such lesions must be excised and subjected to carefully selected IHC markers. This study identifies the most common breast lesions sent to our consultation practice, reiterates salient diagnostic features, differential diagnoses and common pitfalls as well as provides a practical approach that can solve most of these diagnostic dilemmas.